Liturgical Practices with Persons with Severe and Profound Mental Retardation - Parmley, Ingram C. (Journal of religion in disability & rehabilitation, 1995)
This paper explores the presence of liturgical practices which enhance sensory participation of persons with mental retardation in the worship setting. Questions that are explored include: Does the addition of sensory stimuli to a worship service for persons with mental retardation add to subjects' ability to participate? Addition of different and unusual stimuli (auditory, visual and olfactory) at specific times in such a service indicated that both music and incense had a positive effect.